Gene therapy and peripheral nerve repair: a perspective - Hoyng, Stefan A.; de Winter, Fred; Tannemaat, Martijn R.; Blits, Bas; Malessy, Martijn J. A.; Verhaagen, Joost (Frontiers in Molecular Neuroscience, 2015)
Clinical phase I/II studies have demonstrated the safety of gene therapy for a variety of central nervous system disorders, including Canavan’s, Parkinson’s and Alzheimer’s disease, retinal diseases and pain. The majority of gene therapy studies in the CNS have used adeno-associated viral vectors (AAV) and the first AAV-based therapeutic, a vector encoding lipoprotein lipase, is now marketed in Europe under the name Glybera. These remarkable advances may become relevant to translational research on gene therapy to promote peripheral nervous system (PNS) repair. This short review first summarizes the results of gene therapy in animal models for peripheral nerve repair. Secondly, we identify key areas of future research in the domain of PNS-gene therapy. Finally, a perspective is provided on the path to clinical translation of PNS gene therapy for traumatic nerve injuries. In the latter section we discuss the route and mode of delivery of the vector to human patients, the efficacy and safety of the vector, and the choice of the patient population for a first possible proof-of-concept clinical study.